Novel Therapies for Thyroid Autoimmune Diseases. Issue 6 (2nd June 2016) - Fallahi, Poupak; Ferrari, Silvia Martina; Elia, Giusy; Nasini, Francesco; Colaci, Michele; Giuggioli, Dilia; Vita, Roberto; Benvenga, Salvatore; Ferri, Clodoveo; Antonelli, Alessandro
ABSTRACT: C-X-C chemokine receptor (CXCR)3 and its interferon(IFN)γ-dependent chemokines (CXCL10, CXCL9, CXCL11) are implicated in the immune-pathogenesis of autoimmune thyroiditis (AT), Graves disease (GD) and Graves Ophthalmopathy (GO). In tissue, recruited Th1 lymphocytes produce IFNγ, enhancing the tissue secretion of IFNγ-inducible chemokines, initiating and perpetuating the autoimmune process. Patients with AT (with hypothyroidism), and with GO and GD, particularly in the active phase, have high IFNγ-inducible chemokines. Peroxisome proliferator-activated receptor (PPAR)γ or -α agonists and methimazole exert an immune-modulation on CXCR3 chemokines in AT, GD and GO. Other studies are ongoing to evaluate new molecules acting as antagonists of CXCR3, or blocking CXCL10, in Hashimoto thyroiditis (HT), GD and GO. Recently, novel molecules targeting the various agents involved in the pathogenesis of GO, such as rituximab, have been proposed as an alternative to corticosteroids. However, randomized and controlled studies are needed to generalize these interesting results.